If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12m + 4n + -6m + 9n = 0 Reorder the terms: 12m + -6m + 4n + 9n = 0 Combine like terms: 12m + -6m = 6m 6m + 4n + 9n = 0 Combine like terms: 4n + 9n = 13n 6m + 13n = 0 Solving 6m + 13n = 0 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-13n' to each side of the equation. 6m + 13n + -13n = 0 + -13n Combine like terms: 13n + -13n = 0 6m + 0 = 0 + -13n 6m = 0 + -13n Remove the zero: 6m = -13n Divide each side by '6'. m = -2.166666667n Simplifying m = -2.166666667n
| Wow=suchCake | | 6x^2+54=108 | | 2(9X)+2(8X)=68 | | roman=lie | | 18(t-6)+3t=7(3t+2)-8 | | X+2x+4=34 | | 11c-4c= | | swag=pie | | 12-1/3u=12 | | y=8(8)+4 | | (w-5)/(w-1)=(w+2)/(w-3)+1 | | 2x-5=12-45 | | 16(3x-4)=4(12x+1) | | y=8(8)+7 | | 0.36=x/x | | 10pr+8p-5sr-4s= | | 1+2(3x-4)=3(5-x)-4 | | 2x^2-15x+7/6x^2-3x | | (275)(38/55)(11/25) | | x^2-2x=(7+x) | | (w-3)(w-7)=0 | | 4/17(x)=28 | | -3x+4=-2-2x | | (7r-4)(3r-9)=0 | | yw-4w-7y+28= | | -(5y+2)-(-4y-5)=-3 | | (7-u)(5u-8)=0 | | 3(2x-4)=6-3(x+4) | | 3(2x-4)=6-3(x+4) | | s^2-8s-9=0 | | 10t^2+23t-42=0 | | 3(x^2+1)-5x(x^2+x+1)= |